Hubungan Penggunaan Kondom Dengan Perilaku Berisiko Tertular HIV/AIDS Pada Anak Buah Kapal - Darlis, Idhar; Gobel, Fatmah Afrianty; Yusriani, Yusriani (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2019)
In the field of shipping, we know a group of ship crew workers (ABK) who are professions with a high level of mobility. They sail for a long time, days, months, even years, making those who already have a wife / old partner do not meet their wife / partner so that their biological needs are not met. Estimates and projections of the number of people with HIV / AIDS at the age of â‰¥15 years in Indonesia in 2017 were 628,492 people with a number of new infections as many as 46,357 people and deaths as many as 40,468 people. This study aims to determine the relationship of condom use with HIV / AIDS risk behavior among crew members. This study uses a cross sectional study approach. This research was conducted at the Soekarno-Hatta Port of Makassar, with a total sample of 285 respondents. The results of the study found that there was a relationship between the use of condoms and HIV / AIDS risk behavior among crew members. For ABK in sexual intercourse must use a condom as one in preventing the risk of contracting HIV / AIDS